Study on Revitalization of Overseas Employment through the K-Move School Program - Focusing on the USA employment cases of fashion students at P University - Park, HyeSook (International Journal of Advanced Culture Technology(IJACT), 2020)
P University applied for the overseas expansion project of K-Move School operated by Human Resources Development Service of Korea, and was selected twice in 2016 and 2017 to operate the program. The goal of this study was to prepare an activation plan based on the results of the training program to enter the fashion industry in LA, USA. The lack of research It was confirmed that the K-Move School program could provide young people with opportunities to grow into global talents in a situation where it is very uneasy to predict the future based on the domestic employment environment alone. However, in order to successfully expand overseas jobs, systematic and strategic policies are essential by the government and related ministries or institutions so that practical programs suitable for young people can be operated. It is hoped that the results of these studies will be used as basic data for young adults and leaders who are in charge of teaching overseas.